THE CHARACTERISTIC OF ISLAMIC RELIGION AND CHARACTER EDUCATION TEST USING RASCH MODEL - Untung Desy Purnamasari; Samsul Hadi; Edi Istiyono (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Islamic religion and character education is education that provides knowledge and shapes the attitudes, personality, and skills of students in practicing Islamic teachings. To test and assess students' understanding of Islamic religion and character education subjects, a test is held. This study aims to describe the characteristics of the final semester examination on Islamic religion and character education based subject on item response theory. This research was explorative descriptive research. The research subjects were class X students in State Vocational High School 1 Depok taken the final semester examination on subjects of Islamic religion and character education. The object of the research was the question device and all student answer sheets. Data analysis used the Rasch model with Program R in describing good grain characteristics based on the level of difficulty. The results of the analysis showed that from the level of difficulty, there were 26 items from 50 items that must be revised. So, tests of Islamic religion character education need to be evaluated to get a test that meets the requirements and can measure students' abilities.